1997
DOI: 10.1152/jn.1997.77.1.476
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging Assessment of the Human Brain Auditory Cortex Response to Increasing Word Presentation Rates

Abstract: In an investigation of the auditory cortex response to speech, six subjects were studied using echo-planar functional magnetic resonance imaging (fMRI) at 2.1T. The subjects were asked to listen to English nouns presented at various rates ranging from 0 words per minute (wpm) to 130 wpm while fMRI images encompassing their primary and posterior superior secondary auditory cortices were acquired. An asymmetric spin echo imaging sequence was used with an induced T2 weighting of 50 ms to allow for transverse rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
29
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 21 publications
10
29
0
Order By: Relevance
“…Previous publications (Binder et al, 1994;Dhankhar et al, 1997;Buchel et al, 1998;Poldrack et al, 2001;Peelle et al, 2004) and pilot analyses indicated that distinct fMRI profiles could be identified: a linear activation with sentence duration (increasing or decreasing); a step function, i.e., a constant activation collapsing suddenly at the shortest duration (similar to behavioral reports of intelligibility); and a quadratic function, i.e., showing a peak of activation at intermediate durations. One difficulty is that these profiles are nonorthogonal (e.g., there are strong correlations between the linear and step functions and between the step and quadratic functions).…”
Section: Image Acquisition and Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…Previous publications (Binder et al, 1994;Dhankhar et al, 1997;Buchel et al, 1998;Poldrack et al, 2001;Peelle et al, 2004) and pilot analyses indicated that distinct fMRI profiles could be identified: a linear activation with sentence duration (increasing or decreasing); a step function, i.e., a constant activation collapsing suddenly at the shortest duration (similar to behavioral reports of intelligibility); and a quadratic function, i.e., showing a peak of activation at intermediate durations. One difficulty is that these profiles are nonorthogonal (e.g., there are strong correlations between the linear and step functions and between the step and quadratic functions).…”
Section: Image Acquisition and Analysismentioning
confidence: 80%
“…By varying word rate, several studies observed that activation amplitude in regions surrounding the primary sensory cortices varies linearly with stimulus duration (Binder et al, 1994;Dhankhar et al, 1997;Buchel et al, 1998;Poldrack et al, 2001), while other regions show a quadratic variation (Binder et al, 1994;Buchel et al, 1998;Poldrack et al, 2001) or a peak of activation at the fastest presentation rate (Peelle et al, 2004). However, previous studies used block designs, which prevents identification of the temporal response profile and drastically complicates modeling and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…With higher SNR, as in these experiments, recruitment is not observed. As we have discussed before, in conjunction with fMRI of the auditory response in humans, the concept of ''recruitment'' is coupled to SNR and can only be unambiguously claimed to exist if the experiment had infinite SNR (38).…”
Section: Modification Of Saps With Prolonged Exposurementioning
confidence: 99%
“…However, higher presentation rate of nonsense syllables (nontarget stimuli that the subject neglected) may not cause enhanced cortical activity under the DIC condition in regions that are distant from A1; PT, ST, and IF, for example. Recent fMRI studies reported that signal changes in the posterior periauditory regions exhibited a nonlinear (inverted U) relationship to word rate, reaching a peak at about 60 words per minute (wpm) (Bü chel et al, 1998) or at 90 wpm in the primary auditory cortex as well (Dhankhar et al, 1997). Furthermore, frontal regions showed a response to words irrespective of their presentation rate (Bü chel et al, 1998).…”
Section: Functional Differentiation In Multiple Auditory Areasmentioning
confidence: 99%